Development of Hair Tonic with a Combination of Bitter Melon Leaves Extract (Momordica charantia L) with Stringbean Leaves Extract (Vigna sinensis L) - Setiawan, Ike; S, Partomuan; Purba, Anny Victor (Jurnal EduHealth, 2023)
Beauty long hair is each women dream, many Indonesian natural plants can make healthy hair, one of them is Bitter melon leaves extract (Momordica charantia L) and Stringbean leaves extract (Vigna sinensis L). Bitter melon leaves extract contains flavonoids and long bean leaves extract contains saponin and flavonoids as hair growth in hair tonic and preparations for the stability testing of 4% Bitter melon leaves extract and long bean leaves extract with variant ethanol 96% knowing the activity hair tonic of hair growth in New Zealand’s White rabbits. The results show that hair tonic activity F2 show long maximals New Zealand’s White rabbits hair growth (225,67±3,40 mg is longer than positive control. Physical stability test was carried out for 3 months at 25±2 0C dan 40±2 0C. Dermal acute irritation test is known that the single extract of the irritant index pare leaves is very mild 0-0,4).